The uses of digital technologies in dissertation writing: Perspectives of Argentine graduate students in social sciences and humanities (Journal of Applied Learning and Teaching, 2024)
Digital technologies have transformed both the working practices of postgraduate students and the textual production for scholarly research communication. However, little is yet known about the role played by these technologies in dissertation writing. The aim of this study is to further the understanding of dissertation writing in the digital age from the perspective of Argentine graduate students in Social Sciences and Humanities. Based on a sample of eight doctoral students from Argentine national universities, we conducted a qualitative study drawing on in-depth interviews and documentary analysis. The findings provide insights into digital technologies, their uses, associated benefits and challenges, and ways of learning about them. The study concludes that dissertation writing activities are currently mediated by digital technologies and that these technology-mediated activities are conditioned by individual routines and practices, and by the role played by others in the progress of the manuscript. Additionally, we show that engagement with digital technologies in the dissertation writing process has intensified with the pandemic, becoming a critical skill for building knowledge in the 21st century. Our small-scale study contributes to initiating an understanding of the topic in Latin America and to broadening the global body of knowledge in the research area.